Placentophagy: A Trend, a Myth or a Therapy? - Łeńska-Bąk, prof. UO, Katarzyna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2018)
The article describes the increasingly popular phenomenon of placentophagy. It is becoming more and more common in the First World countries of the West, where a woman can take her placenta home after delivering a baby. It is forbidden under the Polish law. The first part of the text focuses on the origins of placentophagy, the reasons for its popularity and for showcasing motives for which people eat parts of their own bodies. The text explores opinions confirming the positive impact of placenta consumption and the medical evidence refuting the majority of these theses. The second part of the article is in turn focused on practices of treating placenta in traditional culture and the reasons for which placenta consumption was strictly forbidden in the past. Finally, it seeks to explain what has led to the dramatic changes in the perception of placentophagy.